Equine Lacrimal Gland Adenocarcinoma - Muhlbauer, Aline Cristine de Moraes; Ortlieb, Iggor Frederico; de Bastiani, Grasiela; Goetten, André Lucio Fontana; Ramos, Adriano Tony (Acta Scientiae Veterinariae, 2022)
Background: Lacrimal gland adenocarcinoma is an extremely rare malignant neoplasm, with few descriptions in the literature. Therefore, its etiology and treatment are not well understood. The present study aims to report the case of an equine histologically diagnosed with lacrimal gland adenocarcinoma in the lower eyelid region and third eyelid treated by surgical excision and intralesional chemotherapy. Case: A 17-year-old male mixed-breed equine weighing 300 kg was treated in the large animal clinic and surgery sector of the Federal University of Santa Catarina in the city of Curitibanos, Santa Catarina, Brazil. The equine revealed an alert and docile temperament without considerable physiological changes in the physical examination. In the evaluation of the right eye, a tumor mass was observed in the region of the lacrimal gland adhered to the third eyelid and lower eyelid, with a light red ulcerated appearance approximately 7 cm in diameter. Therefore, the surgical excision of the adhered tumor mass was performed, with the subsequent intralesional application of 2 mL of Vincristine Sulfate. In the histopathological evaluation following the surgical excision of the tumor mass, yellowish-white fragments of irregular nodules were observed measuring from 3.5×2.0×1.7 cm to 2.0×0.5×0.3 cm, in addition to microscopy focus clusters of weakly basophilic neoplastic glandular cells, some with a randomly arranged lacy aspect, forming disorganized acinar structures and others showed marking islands of the cells organized in a palisade shape by vascular delicate stroma. The neoplastic cells presented anisocytosis, anisokaryosis, prominent nucleoli sometimes binucleated and with basophilic intracytoplasmic secretory material, delimited by scarce connective tissue. In some areas, there were small foci of inﬁltrated lymphocytes and plasmocytes and areas of necrosis. The mass was surrounded by connective tissue, where red blood vessels were found outside the vessels (hemorrhage), and mitoses were observed two per ﬁeld at high magniﬁcation (40x). After the surgical procedure, it was not possible to follow up and reassess of the patient, so there is no clarification on the possibility of tumor recurrence. Discussion: The case reported is uncommon, being only the second report of adenocarcinoma in the equine lacrimal gland. Therefore, there are few descriptions in the literature about its deﬁned etiology and the best treatment method, although, surgical excision is the method of choice because it is a tumor of high recurrence and invasiveness. In this case, we opted for the exeresis of the tumor mass and later application of chemotherapy, a treatment that was relatively eﬀective, to avoid recurrence and the failure of the technique. In these cases, monitoring the animal after the procedure is recommended, evaluating whether there was tumor recurrence, although this was not possible in the present possible. The third eyelid, lacrimal, and zygomatic salivary glands may be sources of intraorbital neoplasms. These neoplastic processes may have similar histological and behavioral characteristics, and their diﬀerentiation is, therefore, problematic. These structures may be diﬀerentiated based on the anatomical location, however, clinical appearance and symptoms are identical in most cases. Adenocarcinoma in the equine lacrimal gland is a neoplasm considered rare, so it is important to emphasize an accurate diagnosis through histopathological analyses to diﬀerentiate it from other frequent orbital neoplasms in horses, allowing more information about this tumor and establishing diﬀerent treatment methods. Keywords: adenocarcinoma, tumor, equine, histopathology. Título: Adenocarcinoma em glândula lacrimal de equino Descritores: adenocarcinoma, tumor, equino, histopatologia.